Analisis Pengaruh Faktor Internal Bank Umum Syariah terhadap Index of Banking Crisis Periode 2013 - 2020 - Mutiara Septiani Tasya; Tjetjep Djuawarsa; Fifi Afiyanti Tripuspitorini (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to identify the resilience of Islamic commercial banks and examine the internal factors of Islamic banks that are thought to influence them. The resilience of Islamic commercial banks was identified using a modified banking crisis index (IBC) formed from the CAR and NPF ratio proxies, while hypothesis testing used WarpPLS as a tool to partially see the effect of Third-Party Funds, FDR, ROA, and BOPO to IBC. The sample of this research is 8 national private Islamic commercial banks in Indonesia for the period 2013-2020. As a result, 2019-2020 is a condition that has been identified as unable to withstand the crisis due to the disruption of the intermediation function. The results of the path analysis show that TPF has an insignificant negative effect, FDR has a significant positive effect, ROA has a significant negative effect, and BOPO has a significant negative effect on the Banking Crisis Index.